Sensitivity of the neotropical solitary bee Centris analis f. (Hymenoptera, Apidae) to the reference insecticide Dimethoate for pesticide risk assessment - Tadei, Rafaela [UNESP]; Menezes-Oliveira, Vanessa Bezerra; Silva, Cláudia Inês; Silva, Elaine Cristina Mathias da; Malaspina, Osmar [UNESP] (Oxford University Press (OUP), 2023)
Currently, only Apis mellifera is used in environmental regulation to evaluate the hazard of pesticides to pollinators. The low representativeness of pollinators and bee diversity in this approach may result in insufficient protection for the wild species. This scenario is intensified in tropical environments, where little is known about the effects of pesticides on solitary bees. We aimed to calculate the medium lethal dose (LD50) and medium lethal concentration (LC50) of the insecticide dimethoate in the Neotropical solitary bee Centris analis, a cavity-nesting, oil-collecting bee distributed from Brazil to Mexico. Males and females of C. analis were exposed orally to dimethoate for 48 h under laboratory conditions. Lethality was assessed every 24 h until 144 h after the beginning of the test. After the LD50 calculation, we compared the value with available LD50 values in the literature of other bee species using the species sensitivity distribution curve. In 48 h of exposure, males showed an LD50 value 1.33 times lower than females (32.78 and 43.84 ng active ingredient/bee, respectively). Centris analis was more sensitive to dimethoate than the model species A. mellifera and the solitary bee from temperate zones, Osmia lignaria. However, on a body weight basis, C. analis and A. mellifera had similar LD50 values. Ours is the first study that calculated an LD50 for a Neotropical solitary bee. Besides, the results are of crucial importance for a better understanding of the effects of pesticides on the tropical bee fauna and will help to improve the risk assessment of pesticides to bees under tropical conditions, giving attention to wild species, which are commonly neglected.
Sensibilidade da abelha solitária neotropical Centris analis F. (Hymenoptera, Apidae) ao inseticida de referência Dimetoato para avaliação de risco de agrotóxicos
Keywords: Apidae; Ecological risk assessment; Ecotoxicology; Insecticide; Pesticide regulation; Species sensitivity distribution (SSD)